Morphological and molecular evidence of eight new species of the genus Scaptodrosophila Duda (Diptera, Drosophilidae) from China - Peng, Hongen; Lin, Yong; Chen, Hongwei (Zootaxa, 2022)
By integrating morphological and molecular evidences, seven new species of the Scaptodrosophila coracina species group and one new species of uncertain affinity to this genus from China are recognized and described: S. angustifolia sp. nov., S. apunctata sp. nov., S. latifoliacea sp. nov., S. longiciliata sp. nov., S. melanovittata sp. nov., S. polytricapillum sp. nov., S. undulata sp. nov. and S. curvata sp. nov. A key to the examined species is provided. Intra- and interspecific, pairwise p-distances with DNA barcodes (partial sequences of the mitochondrial COI, i.e., cytochrome c oxidase subunit I gene) are calculated and summarized. In addition, S. zebrina Liu & Chen, 2018 from Yunnan, China is recognized as junior homonym of S. zebrina (Bezzi, 1928) and renamed as S. zebromyia nom. nov.